A systematic review of gamified learning motivation for English language among undergraduates - Chen, Minjuan; Tan, Wee Hoe; Lee, Sze Seau; Sun, Jiaming (International Journal of Evaluation and Research in Education (IJERE), 2025)
Undergraduate students’ motivation for learning English as a foreign language (EFL) is influenced by multiple factors, yet traditional teaching methods often fail to sustain engagement, leading to learning disengagement and sub-optional outcomes. The increasing integration of gamified learning has shown potential in addressing this challenge, but its effectiveness remains unclear, necessitating a systematic synthetic of existing research. This systematic review employs the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework to examine 313 studies retrieved from Education Resources Information Center (ERIC),Web of Science (WoS), and Scopus, narrowing them down to 36 relevant articles. The review categorizes findings into five key themes: i) teaching techniques and strategies; ii) learning environments and styles; iii) psychological and cultural factors; iv) technological support; and v) individual learner variables. The results highlight the positive impact of game-based learning, personalized instruction, and technology-enhanced approaches to motivation. However, psychological challenges, such as burnout and anxiety, remain significant barriers. The studyreveals research gaps, particularly regarding the long-term impact of gamified learning on EFL motivation, underscoring the need for further empirical investigation to optimize gamification strategies in EFL education.